“No Viral No Education”: Strengthening Prosecutors’ Competence and Servant Leadership through Islamic Education - Octavianne, Helena; Suhariadi, Fendy; Mudzakkir, Mohammad Fakhruddin; Sarwestri, Katarina Endang (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
The phenomenon of “no viral no education” reflects how viral issues on social media often become the main trigger for raising public awareness and attention toward various problems, including those in education and law. This study aims to analyze the role of this phenomenon in developing prosecutors' competencies and applying servant leadership from the perspective of Islamic education. This research uses a qualitative approach with literature studies and secondary data analysis from relevant sources. The findings indicate that the virality of an issue can push prosecutors to enhance their competencies by exposing them to cases that attract public attention, requiring them to be more professional, transparent, and accountable. Moreover, the concept of servant leadership in Islamic education emphasizes leadership that serves and prioritizes the well-being of society. In this context, the “no viral no education” phenomenon shapes prosecutors into more responsive, fair, and Islamic value-based leaders. This study recommends using social media as an educational tool for legal awareness and strengthening servant leadership values within the justice system. Academically, this study contributes to the discourse on legal reform and leadership by linking contemporary digital culture with Islamic educational values. This study builds a bridge between public accountability demands driven by social media and the ethical foundations of servant leadership in Islam, while also opening opportunities to integrate Islamic values into modern legal practice.. The study also recommends utilizing social media as an alternative educational platform to promote legal literacy and to strengthen servant leadership within the justice system. Fenomena “no viral no education” mencerminkan bagaimana isu-isu viral di media sosial sering menjadi pemicu utama tumbuhnya kesadaran dan perhatian publik terhadap berbagai persoalan, termasuk di bidang pendidikan dan hukum. Penelitian ini bertujuan untuk menganalisis peran fenomena tersebut dalam pengembangan kompetensi jaksa dan penerapan kepemimpinan melayani (servant leadership) dalam perspektif pendidikan Islam. Penelitian ini menggunakan pendekatan kualitatif dengan studi kepustakaan dan analisis data sekunder dari berbagai sumber yang relevan. Temuan menunjukkan bahwa viralnya suatu isu dapat mendorong jaksa untuk meningkatkan kompetensinya, terutama ketika mereka menangani kasus-kasus yang mendapat sorotan publik, sehingga dituntut untuk bekerja lebih profesional, transparan, dan akuntabel. Konsep kepemimpinan melayani dalam pendidikan Islam sendiri menekankan pada kepemimpinan yang berorientasi pada pelayanan dan kesejahteraan masyarakat. Dalam konteks ini, fenomena “no viral no education” berperan dalam membentuk karakter jaksa agar lebih responsif, adil, dan berlandaskan nilai-nilai keislaman. Secara akademik, penelitian ini memberikan kontribusi terhadap diskursus reformasi hukum dan kepemimpinan dengan mengaitkan budaya digital kontemporer dengan nilai-nilai pendidikan Islam. Studi ini membangun jembatan antara tuntutan akuntabilitas publik melalui media sosial dan etika kepemimpinan melayani dalam Islam, serta membuka peluang integrasi nilai-nilai Islam dalam praktik hukum modern. Penelitian ini juga merekomendasikan pemanfaatan media sosial sebagai sarana edukasi alternatif untuk meningkatkan literasi hukum dan memperkuat nilai-nilai kepemimpinan melayani dalam sistem peradilan.